Immediate load unit implants: possibility of oral and aesthetic rehabilitation – literature review (Research, Society and Development, 2021)
Tooth loss happens for several reasons and brings bad consequences for the individual's oral health, including social and aesthetic disorders, constituting a challenge for the dental field. The use of implants to improve function, esthetics and oral health advanced from the concept of osseointegration, evolved from conventional protocols with two surgical phases for immediate implantation after extraction, including immediate loading, enabling the oral rehabilitation of total and partial edentulous and a single element. The aim of this study was to conduct a literature review on the possibility of rehabilitation in unit rehabilitation with implants under immediate load. The research was conducted through a bibliographic survey of articles, dissertations, journals and publications on unit implants with immediate loading, indexed in Scielo, Pubmed, Medline, Google Scholar databases, in a period between the years 2015 to 2020. Literature it is broad and demonstrates high success rates and predictability of implants with immediate loading, being a very beneficial procedure for the patient due to the reduction of total treatment time, cost reduction and very satisfactory results, including when it comes to aesthetics and patient satisfaction. patient. It is possible to perform immediate implants and immediate rehabilitation even in infected areas, safely and effectively, as long as you follow all the necessary precautions for each situation, both in the surgical procedure and in the care of the patient after surgery. In all cases, the use of implants with immediate loading requires careful planning.